Modification of triphenylphosphonium lipophilic cations for mitochondrial delivery - Ong, How Chee (Nanyang Technological University, 2022)
Triphenylphosphonium (TPP+) moieties, when conjugated to a molecule of interest, results in greater mitochondrial accumulation relative to the unconjugated cargo. However, while TPP+ moieties are known to be effective at conferring mitochondrial-targeting abilities to molecules, modifications to the structure of the TPP+ moiety itself is relatively rare. Instead, the key modifications employed to tune molecular properties is by altering the structure of the linker, rather than the phosphine used. However, the lack of controlled studies comparing the two contrasting methodologies impedes the general adoption of modified TPP+ as mitochondrial vectors. In addition, the functionalization of TPP+ has been mostly limited to the incorporation of simple functional groups into the TPP+ moiety. In light of these issues, there is a pressing need for both systematic studies on the topic, as well as the development of novel TPP+ species. In this work, we synthesized modified triphenylphosphonium moieties, examined its effects on steric and electronic properties, as well as its corresponding effect on mitochondrial delivery.